EDUKASI LAKTASI BERBASIS ANDROID EFEKTIF MENINGKATKAN PENGETAHUAN IBU HAMIL - Fauzia Djamilus; Sri Mulyati; Novita Dewi Pramanik; Dedes Fitria (Poltekkes Kemenkes Bandung, 2025)
In 2023, the national coverage of exclusive breastfeeding was just slightly above half. The figure was even lower in West Java. The primary issue is the suboptimal practice of exclusive breastfeeding. This study aimed to analyze the effectiveness of Android-based lactation education in increasing the knowledge of third-trimester pregnant women about exclusive breastfeeding. The study employed a quasi-experimental design with a pre and post-test without a control group approach. The population consisted of third-trimester pregnant women in Bogor City, with a sample of 37 participants selected through a multi-stage random sampling technique. The intervention provided education on exclusive breastfeeding through images and animated videos on an Android application. The analysis employed includes descriptive analysis and the Wilcoxon signed-rank test. The research findings indicate a significant difference (p=0.000) in the knowledge of pregnant women, with the average knowledge increasing from 76.29 before the intervention to 83.81 after the intervention. Respondents found the application to be fairly communicative, with some suggestions for improvement. The Android application has the potential to enhance pregnant women's knowledge about lactation, serving as an innovative strategy to support the success of exclusive breastfeeding.